Pekanbaru City Livestock Marketing With Android-Based Applications - Yuvi Darmayunata; Latifa Siswati; Anto Aryanto (Yayasan Riset dan Pengembangan Intelektual (YRPI), 2021)
This research was conducted to provide solutions to cattle breeders in Pekanbaru City, especially in Rumbai District. Cattle breeders always have difficulty selling cows due to middlemen and coupled with the pandemic period due to the Covid 19 virus, thus making cattle sales decline every year. In increasing the sale of cattle during this pandemic is to use technology as a marketing solution. The technology used in the research is android based. With an Android base, consumers and producers will be integrated with each other so that the buying and selling process becomes easier. The purpose of this study is to help cattle sellers in marketing cattle so that the buying and selling process becomes easy. The method used is Unified Modeling Language (UML) in designing this system. The results show the success of designing applications for cattle sellers, applications can help farmers market their cattle, information about cattle prices to be compared in livestock groups can be seen so as to minimize fraud because buyers can directly see the price of the cattle.